Analisis Peningkatan Kuantitas dan Kualitas SDM Di Bursa Efek Indonesia Kp.Sumut - Ibnu Habib Wahyudi; Marliyah Suryadi (Jurnal of Management and Social Sciences, 2023)
Human resources (HR) is a crucial factor in any organization. The success of an organization is greatly influenced by the quality and quantity of its human resources, which impact performance achievements. One of the issues faced by PT. Bursa Efek Indonesia Kp.Sumut during the author's internship is the insufficient quantity of employees. The aim of this research is to empirically understand the increase in both quantity and quality of human resources (HR) as a solution to the issues at PT. Bursa Efek Indonesia Kp.Sumut. This study utilizes a descriptive method, where the problem-solving procedures investigated depict the condition of the subject or object based on observable facts. Data collection methods include observation, interviews, and documentation. Based on the research findings, several conclusions can be drawn. To address the issues of quantity and quality of HR at PT. Bursa Efek Indonesia Kp.Sumut, the company needs to enhance HR through recruitment, selection, human resource planning, and performance evaluation.